Atypical parkinsonism and self‐mutilation: A new lens on the old concept. Issue 7 (9th July 2021) - Salari, Mehri; Etemadifar, Masoud; Ghanbari, Kimia
Abstract: We report a case of atypical parkinsonism and self‐mutilation. Abstract : We report a case of atypical parkinsonism and self‐mutilation.